Управление гребными двигателями электроходов на маневрах - Яровенко, Владимир Алексеевич; Зарицкая, Елена Игоревна (НТУ "ХПИ", 2016)
Обоснована целесообразность поиска оптимальных законов управления гребными электродвигателями электроходов по показателям качества работы судна, как старшей системы. Представлена стратегия, предложен метод и описана процедура поиска оптимальных решений. Найдены оптимальные законы управления асинхронными частотно-управляемыми гребными электродвигателями при разгоне и торможении электроходов. Проведен сравнительный анализ работы пропульсивных комплексов при управлении по классическим и найденным оптимальным законам управления. Проиллюстрирована эффективность предложенного метода поиска оптимальных решений.

Investigations were carried out in relation to asynchronous frequency-controlled propulsion motors. Known laws of optimal control of asynchronous electric motors for propulsion electric drives are not suitable. The expediency of searching optimal laws of propulsion motors’ control in terms of the quality of the ship’s operation as the senior system is grounded. To solve these problems propulsion motors are considered as part of a single ship's propulsion complex. The structure included its heat engines, electric propulsion plant, wheel, screws and ship’s hull. A special optimization method was developed. It showed high efficiency to solve the given tasks. The strategy was presented and the procedure of search for optimal solutions was described. The parameters that affect the quality of the vessel’s performance were found. The optimal control laws of asynchronous frequency-controlled propulsion motors during electric vessels’ acceleration and braking were found out. The research results cover a large class of vessels. A comparative analysis of the results of the control in terms of classic and discovered optimal laws was conducted. High efficiency of the proposed method, of search for optimal solutions was illustrated.
Control of electric vessels’ propulsion motors on maneuvers
Keywords: гребные двигатели; электроходы; маневрирование судов; оптимальное управление; системный подход